HealthPathways implementation in a New Zealand health region: a qualitative study using the Consolidated Framework for Implementation Research. Issue 12 (31st December 2018) - Stokes, Tim; Tumilty, Emma; Doolan-Noble, Fiona; Gauld, Robin
Abstract : Objectives: To explore the process of implementation of an online health information web-based portal and referral system (HealthPathways) using implementation science theory: the Consolidated Framework for Implementation Research (CFIR). Setting: Southern Health Region of New Zealand (Otago and Southland). Participants: Key Informants (providers and planners of healthcare) (n=10) who were either involved in the process of implementing HealthPathways or who were intended end-users of HealthPathways. Methods: Semistructured interviews were undertaken. A deductive thematic analysis using CFIR was conducted using the framework method. Results: CFIR postulates that for an intervention to be implemented successfully, account must be taken of the intervention's core components and the adaptable periphery. The core component of HealthPathways—the web portal and referral system that contains a large number of localised clinical care pathways—had been addressed well by the product developers. Little attention had, however, been paid to addressing the adaptable periphery (adaptable elements, structures and systems related to HealthPathways and the organisation into which it was being implemented); it was seen as sufficient just to deliver the web portal and referral system and the set of clinical care pathways as developed to effect successful implementation. In terms of CFIR's 'inner setting' corporate and professional cultures, the implementation climate and readiness for implementation were not properly addressed during implementation. There were also multiple failures of the implementation process (eg, lack of planning and engagement with clinicians). As a consequence, implementation of HealthPathways was highly problematic. Conclusions: The use of CFIR has furthered our understanding of the factors needed for the successful implementation of a complex health intervention (HealthPathways) in the New Zealand health system. Those charged with implementing complex health interventions should always consider the local context within which they will be implemented and tailor their implementation strategy to address these.